The far-infrared/radio correlation for a sample of strongly lensed dusty star-forming galaxies detected by Herschel. Issue 1 (27th January 2022) - Giulietti, M; Massardi, M; Lapi, A; Bonato, M; Enia, A F M; Negrello, M; D'Amato, Q; Behiri, M; De Zotti, G
ABSTRACT: We investigate the radio/far-infrared (FIR) correlation for a sample of 28 bright high-redshift (1 ≲ z ≲ 4) star-forming galaxies selected in the FIR from the Herschel -ATLAS fields as candidates to be strongly gravitationally lensed. The radio information comes either from high sensitivity dedicated Australia Telescope Compact Array observations at 2.1 GHz or from cross-matches with the FIRST survey at 1.4 GHz. By taking advantage of source brightness possibly enhanced by lensing magnification, we identify a weak evolution with redshift out to z ≲ 4 of the FIR-to-radio luminosity ratio q FIR . We also find that the q FIR parameter as a function of the radio power L_1.4 GHz displays a clear decreasing trend, similarly to what is observed for optically/radio-selected lensed quasars found in literature, yet covering a complementary region in the q_FIR\!-\!L_1.4 GHz diagram. We interpret such a behaviour in the framework of an in situ galaxy formation scenario, as a result of the transition from an early dust-obscured star-forming phase (mainly pinpointed by our FIR selection) to a late radio-loud quasar phase (preferentially sampled by the optical/radio selection).